Droit et linguistique - une approche du formalisme juridique - Raucent, Léon (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
Recent works in linguistics and on the philosophy of interpretation have some relevance for lawyers, since law can be characterized to a certain extent, especially in an age of burgeoning legislation, as a language-related science, as an exercise in reading the text of statutes. The textual basis of law explains why laymen are so frequently complaining about its formal nature, i.e. its almost exclusive concern with words rather than concepts, and its total disregard for social reality. To say that such criticism can be explained is not, however, saying that it is valid. This paper attempts to show that the close reliance of law on the wording of legislation does not, or at least should not, lead to formalism. For the meaning of legislation is derived not only from its own words, but also from its context and social background. Indeed, legislation can only acquire its ultimate and complete meaning through its application to individual cases.